An Understanding of the Global Status of Major Bacterial Pathogens of Milk Concerning Bovine Mastitis: A Systematic Review and Meta-Analysis (Scientometrics) - Krishnamoorthy, Paramanandham (Pathogens, 2021)
In this study, the major mastitis pathogen prevalence in the cattle and buffalo of the world was estimated by a meta-analysis. Staphylococcus (S) species, Streptococcus (St) species, and Escherichia coli (Ec) prevalence studies reported during 1979–2019 were collected using online databases, and offline resources. A meta-analysis of these data was done with the meta package in R-Software. The Staphylococcus aureus was the major mastitis pathogen, mostly causing subclinical mastitis, Ec causing clinical mastitis and St causing subclinical and clinical mastitis. The pooled prevalence estimates of S, St, and Ec were 28%, 12%, and 11% in the world from 156, 129, and 92 studies, respectively. The S, St, and Ec prevalences were high in Latin America (51%), Oceania (25%), and Oceania (28%), respectively. Higher S, St, and Ec prevalences were observed by molecular methods, signifying high sensitivity and usefulness for future studies. Among bacterial species, S. aureus (25%) followed by coagulase-negative Staphylococcus species (20%), Escherichia coli (11%), St. agalactiae (9%), St. uberis (9%) were the important pathogens present in the milk of the world. We hypothesize that there is a urgent need to reduce mastitis pathogen prevalence by ensuring scientific farm management practices, proper feeding, therapeutic interventions to augment profits in dairying, and improving animal and human health.